China ”“ Falta um Discurso sobre a Ascensão Pacífica Terrestre: A Nova Rota das Sedas (Meridiano 47 - Journal of Global Studies, 2017)
The current relations between the Communist Government in Beijing and the countries that surround it are characterized as both ambiguous and obscure. In that sense, it creates concern about the growth of its economic and political influence in the region, especially with regard to Central Asia. Thus, and making use of an historical analysis, this article aims to analyze the possible meanings and origins of the rising Chinese presence in its neighbor regions, especially in Central in Southeast Asia.